Pengaruh Tingkat Suku Bunga Kredit dan Jumlah Simpanan Masyarakat terhadap Jumlah Kredit pada Bank Umum Pemerintah di Indonesia - Ni Putu Rediatni Giri; I Komang Darma Setiawan (Warmadewa Economic Development Journal (WEDJ), 2019)
Bank giving service to it`s customer in two way, conventional system or syariah system. The aims of this research is to analyze the simultan and partial effect of interest of credit and three partij fund to amount of credit in bank government in Indonesia. the data has been analysed by using multiple regression linear, t-test, and F-test. The result shows that in simultan interest of credit and three partij fund have a signifficant effect to amount of credit. In partial, interest of credit have no signifficant effect while three partij fund have a positive and signifficant effect to amount of credit. R2 shows that 83,9 percent variation of interest of credit and three partij fund can describe the effect of both to amount of credit. While, 16,1 percent has describe by other variables out of model.